2020
DOI: 10.1016/j.jhydrol.2020.125600
|View full text |Cite
|
Sign up to set email alerts
|

Agent-based modelling and flood risk management: A compendious literature review

Abstract: The use of agent-based modelling (ABM) to tackle flood-related risk challenges is becoming increasingly popular in recent years. This paper reviews the literature at the interface of ABM and flood-related studies in view of understanding the technique's advantages and limitations to flood risk management, based on a set of 61 representative articles. In particular, to understand how this process-based technique can help to link human (also institutional) decisions and behaviour with flood risks through the who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 119 publications
(149 reference statements)
0
33
0
Order By: Relevance
“…2.3.1). Direct validation of agent-based models is a grand challenge as such models are aimed to study non-observable scenarios, where there is uncertainties associated with the emergent nature of behaviours and where validation datasets of such type are not available (An et al, 2020;Zhuo et al, 2020;Aerts 2020). One alternative approach is a component-wise validation (Bert et al, 2014).…”
Section: Evaluation Of the New Characteristics And Rulesmentioning
confidence: 99%
See 1 more Smart Citation
“…2.3.1). Direct validation of agent-based models is a grand challenge as such models are aimed to study non-observable scenarios, where there is uncertainties associated with the emergent nature of behaviours and where validation datasets of such type are not available (An et al, 2020;Zhuo et al, 2020;Aerts 2020). One alternative approach is a component-wise validation (Bert et al, 2014).…”
Section: Evaluation Of the New Characteristics And Rulesmentioning
confidence: 99%
“…Most of the existing evacuation models are built upon the soft agent-based modelling (ABM) paradigm, as it offers the flexibility needed to represent both the interactive and the collective responses of people, either considered as moving individuals, groups of individuals in a vehicle, or household units (Zhuo and Han, 2020;Aerts, 2020). Incorporating these responses into ABM-based models enables to simulate people response dynamics into the flood risk analysis, leading to more informed predictions for flood adaptation planning and extraction of decision-relevant indicators (Aerts et al, 2018;McClymont et al, 2019).…”
mentioning
confidence: 99%
“…Recently, reviews specific to the use of ABMs in the area of FRMA have been published by Aerts (2020), Taberna et al (2020), Zhuo and Han (2020), and Simmonds et al (2020). Aerts (2020) compared trends among other system dynamic models and discussed the decision-making process associated with human behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Taberna et al (2020), looked at ABM implementation across disciplines (from an economic and a flood viewpoint) and sheds light on different spatio-temporal scales, and the learning process in agents to change adaptive behaviour. Zhuo and Han (2020), identified spatial distributions of the studies, different ABM platforms, their applications and advantages. Notably, the study identified three main challenges of ABM simulation: model development, assessment, and documentation.…”
Section: Introductionmentioning
confidence: 99%
“…There is a review of agentbased modeling for simulation of agricultural systems (Mora-Herrera et al, 2021). Zhuo and Han's (2020) paper reviews agent-based modelling and flood risk management. Additionally, Macal's (2016) study addresses the background and current state of the field of agent-based modelling and simulation.…”
Section: Introductionmentioning
confidence: 99%